Teacher Professional Transformation Through Learning Community Management: A Literature Review - Nurhadi, Nurhadi; Purnama, Syahfitri (Literasi: Jurnal Ilmu Pendidikan, 2025)
The Professional Learning Community (PLC) serves as a means of contextual teacher professional transformation that aligns with the school environment, particularly in addressing instructional challenges. This study examines the gap between the conceptual framework of PLCs as defined in the literature and their practical implementation in schools. The research aims to analyze how the management of Professional Learning Communities (PLCs) can promote teachers’ professional transformation in educational settings. Using a literature review approach, this study synthesizes national and international research findings concerning the effectiveness of learning community management in enhancing teachers’ pedagogical competence, collaboration, and professional reflection. The synthesis reveals that effective and sustainable management of learning communities significantly contributes to improving teacher professionalism, especially when implemented through an iterative cycle of initial reflection, planning, implementation, and evaluation. Proper management not only strengthens teachers’ ability to design and conduct contextual learning but also fosters a culture of collaboration and collective responsibility among educators. Nevertheless, a gap remains between the ideal concept of PLCs and their actual practice in schools, particularly regarding management and program sustainability. Therefore, this study emphasizes the importance of applying cyclical management principles and institutional support to ensure that teacher learning communities truly function as strategic mechanisms for professional development that positively impact teaching quality and student learning outcomes.